Body perceptions, occupations, eating attitudes, and behaviors emerged during the pandemic: An exploratory cluster analysis of eaters profiles - Monthuy-Blanc, Johana; Corno, Giulia; Bouchard, Stéphane; St-Pierre, Marie-Josée; Bourbeau, Francisca; Mostefa-Kara, Leïla; Therrien, Émie; Rousseau, Michel (Frontiers in Psychology, 2022)
Introduction COVID-19 pandemic negatively impacted people’s mental and physical health. Three areas have been significantly impacted, among others: eating-related behaviors, occupational balance, and exposure to self-image due to videoconferencing. This study aims to explore and document eaters profiles that were reported during the pandemic in the general Canadian population using a holistic perspective, including body perceptions, attitudes, and eating behaviors (i.e., body image, behaviors, attitudes, and motivations regarding food), and occupations (i.e., physical activity and cooking). Methods This cross-sectional study was conducted from May to September 2020. Two hundred and seventy-three Canada’s residents, French speaking of 18 years of age and older, participated in an online survey on behaviors, attitudes, and motivations regarding food and eating as well as body image and occupations during the COVID-19 pandemic. A hierarchical cluster analysis was used to determine the eaters profiles. One-way ANOVA and Chi-square test were conducted to differentiate occupational characteristics between eaters profiles. Results Three distinctive profiles were found during the COVID-19 pandemic and could be placed on a continuum: the Congruent-driven eater is at the functional pole of the continuum, whereas the Incongruent-driven eater is at the dysfunctional pole of the eaters continuum. In the middle of the continuum, the Incongruent-perceptual eater is at a critical crossing point. Significant differences were reported between eaters profiles. Discussion The empirical results based on an eaters continuum conceptualization highlight the importance of understanding how people perceive their body to assess and promote food well-being.